Identification of the metabolites of myricitrin produced by human intestinal bacteria in vitro using ultra-performance liquid chromatography/quadrupole time-of-flight mass spectrometry. (July 2014) - Du, Le-yue; Zhao, Min; Xu, Jun; Qian, Da-wei; Jiang, Shu; Shang, Er-xin; Guo, Jian-ming; Liu, Pei; Su, Shu-lan; Duan, Jin-ao; Leng, Xue-jiao
Abstract : Objective: To investigate the metabolic routes and metabolites of myricitrin, an important active ingredient of traditional herbal medicine, yielded by the isolated human intestinal bacteria, which have not been reported previously. Methods: Fresh human fecal samples were collected from a healthy female volunteer and about 100 different bacterial colonies were isolated. Ultra-performance liquid chromatography/quadrupole time-of-flight mass spectrometry technique combined with Metabolynx™ software was used for analysis of the metabolic profile of myricitrin by the isolated human intestinal bacteria. Results: One hundred different bacterial colonies, which developed on plates, were picked up, and four of them were further identified by using the technique of 16S rRNA gene sequencing due to their relatively strong metabolic capacity toward myricitrin. Most of them belong to Escherichia. Parent compound and three metabolites (quercetin-3- O -rhamnoside, myricetin and quercetin) were detected in the isolated bacterial samples compared with blank samples. The metabolic pathways of myricitrin included deglycosylation and dehydroxylation. Conclusions: These metabolites suggested that myricitrin was first dehydroxylated to quercetin-3- O -rhamnoside and subsequently deglycosylated to quercetin. Additionally, myricitrin could also be deglycosylated to the aglycon myricetin. Moreover, those metabolites might influence the biological effect of myricitrin in vivo, which led to affect the clinical effects of the medicinal plants and traditional herb medicines.